JAIVAMANUSHYAN - anand (kottayam D C BOOKS, 1991)
A brilliant study about man and society. Anand explores man from pre-historic times as a nomad to the tech-savvy modern man and how his views form the society around him.
KERALA SAHITYA ACADEMY AWARD
Keywords: MAN AND SOCIETY